Severe periodontitis is associated with systemic inflammation and a dysmetabolic status: a case–control study - Luigi Nibali (Blackwell Synergy, 2007)
Background and Aim: A cluster of metabolic factors defines a syndrome that predisposes to diabetes and cardiovascular disease. Chronic infections such as periodontitis might alter these individual metabolic factors and the systemic inflammatory burden. The aim of this study was to investigate the association between severe periodontitis and increase in inflammatory and metabolic risk factors for cardiovascular disease. Materials and Methods: We examined 302 patients with severe periodontitis and 183 healthy controls, and we collected a blood sample from each subject in order to investigate differences in inflammatory (leukocyte numbers and differential counts) and metabolic markers (lipids and glucose). Results: After correcting for differences in age, gender, smoking and ethnicity, periodontitis subjects exhibited a low-grade systemic inflammation (increased white cell counts, 1.10 1.02 109/l, 95%CI 1.05–1.15, p50.0001), dyslipidemia [lower high-density lipoprotein cholesterol, 1.14 1.03 mmol/l, 95%CI 1.08–1.20, po0.0001 and higher low-density lipoprotein cholesterol, 1.12 1.03, 95%CI 1.05–1.19, po0.0001) and increased non-fasting serum glucose levels (1.04 1.01 mmol/l, 95%CI 1.02–1.06, p50.01) when compared with controls. The associations were confirmed in a subpopulation of Caucasian non-smokers. A trend for a dose dependent effect of the number of periodontal pockets on the tested inflammatory and metabolic markers was observed. Conclusions: These data suggest a possible link between severe generalized periodontitis, systemic inflammation and a dysmetabolic state in otherwise healthy individuals.